Language use in edisi siasat : Changing hues in Malaysian media presentation? / Kamisah Ariffin, Roselina Musahar, and Misyana Susanti Husin - Ariffin, Kamisah; Musahar, Roselina; Husin, Misyana Susanti (Universiti Teknologi MARA Cawangan Pahang, 2006)
When Edisi Siasat was first aired on NTV7, the approach of presenting the issues through the presenter’s outrageous use of language did not go unnoticed by the public. It is claimed by some as ‘a breath of fresh air on Malaysian TV’. In other words, rather than approaching issues that are considered sensitive to the Malaysian communities ‘in the usual preachers’ fashion so beloved by the Malaysian mainstream media’, this programme ‘expresses the outrage the way one would while having an impassioned chat over teh tarik at the local mamak stall’ (Ziad Razak 2003). However, there are also viewers who regard such approach as being insensitive toward the Malaysian way of communicating. This paper looks at the approach of the programme from the aspect of language use and the public’s perception toward such use in the media.